2018
DOI: 10.1186/s12879-018-3021-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting time to sputum culture conversion and treatment outcome of patients with multidrug-resistant tuberculosis in China

Abstract: BackgroundFew prospective cohort studies, none in China, have investigated the relationship between treatment outcomes of multidrug-resistant tuberculosis (MDR-TB) patients and sputum culture conversion. Factors affecting the time of the culture conversion throughout the whole course of the treatment have rarely been investigated.MethodsThis study was performed in four cities in Jiangsu province, China. MDR-TB patients were consecutively enrolled between December 2011 and March 2014. Rates of sputum culture co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 28 publications
8
44
1
Order By: Relevance
“…However, further research should investigate the validity of SCC at different timepoints as an early predictor of treatment efficacy, as it may differ by regions with different HIV prevalence, capacities for MDR-TB treatment, and drug resistance patterns (12,13). For example, the 6-month SCC had stronger association with cure than 4-month SCC among Pakistan patients (7), while studies conducted in China and Ethiopia showed that the optimum time point of achieving SCC for predicting successful treatment outcome was between four to six months (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further research should investigate the validity of SCC at different timepoints as an early predictor of treatment efficacy, as it may differ by regions with different HIV prevalence, capacities for MDR-TB treatment, and drug resistance patterns (12,13). For example, the 6-month SCC had stronger association with cure than 4-month SCC among Pakistan patients (7), while studies conducted in China and Ethiopia showed that the optimum time point of achieving SCC for predicting successful treatment outcome was between four to six months (26).…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating potential predictors of SCC in MDR-TB could help identify patients who are likely to develop poor outcomes and prompt clinical intervention to improve treatment outcomes for these individuals. Numerous studies have been conducted to investigate the predictors for MDR-TB treatment outcomes (11)(12)(13), but few have been carried out in China. We therefore designed a retrospective cohort study to evaluate the SCC and identify its predictors among MDR-TB patients in Hangzhou in eastern China.…”
Section: Introductionmentioning
confidence: 99%
“…Sputum conversion plays an important role in the management of tuberculosis because it determines response to TB treatment [6,7] . Prognosis of the patient is determined by negativity or positivity of the sputum results.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless the MDR-TB treatment regime (12 or 24 months), the WHO recommend the using sputum smear or culture conversion as a proxy marker for a successful MRD-TB treatment outcome [1]. Recently, many efforts have been made to validate these MDR-TB treatment e cacy markers including the optimal time of measurement and the in uencing factors [2][3][4][5][6][7][8][9][10]. One of these studies concluded that the validity of culture conversion is signi cantly higher than sputum smear conversion, and the four months schedule is a common optimal time for culture and smear conversion [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies concluded that the validity of culture conversion is signi cantly higher than sputum smear conversion, and the four months schedule is a common optimal time for culture and smear conversion [10]. Nevertheless, the in uencing factors of time-to initial sputum smear and culture conversions varied from one study to another [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%